A COMPARATIVE STUDY OF THE TAX ACCOUNTING PROCESS BETWEEN LIMITED COMPANIES AND JOINT STOCK COMPANIES FROM THE POINT OF VIEW OF THE TAX ADMINISTRATION FOR THE AUDITOR'S REPORT (World Economics and Finance Bulletin, 2023)
The study aims to clarify the role of the auditor in enhancing the reliability of the financial statements submitted by the taxpayer to the tax administration through his audit procedures. Explaining the reasons for the tax administration resorting to estimation according to the annual controls in the process of tax accounting with taxpayers, and the extent to which it adopts the auditor’s report and the financial statements in the process of determining the income tax base, thus activating tax accounting using the self-assessment method, reducing cases of tax evasion, and reducing the gap between the parties to the tax accounting process. (Tax administration, auditor, and taxpayer). This study reached a set of results and recommendations, including that the tax administration uses the lists audited by the auditor as a basis for determining the income tax base for joint-stock companies. That is, the tax accounting process in joint-stock companies boils down to amending the accounting profit shown in the accounts submitted to the Tax profit. This means that there is confidence regarding the financial statements of joint-stock companies, unlike the financial statements of limited companies. The study recommends the need to urge companies to commit to preparing financial statements in accordance with approved accounting systems, local accounting rules, and relevant legal requirements, which would increase confidence and credibility in these lists and lead to avoiding manipulation in the preparation of financial statements or trying to conceal a specific paragraph or element of the lists. Finance
Keywords: taxpayer; joint stock and limited companies; financial statements